Challenging the One-Size-Fits-All Approach in Rheumatoid Arthritis Management by Addressing Serostatus-Driven Differences - Andrei-Flavius Radu; Ada Radu; Carmen Delia Nistor-Cseppento; Delia Mirela Tit; Lavinia Cristina Moleriu; Nicoleta Anamaria Pascalau; Radu Dumitru Moleriu; Simona Gabriela Bungau (Balneo and PRM Research Journal, 2025)
International rheumatoid arthritis (RA) guidelines do not differentiate treatment strategies based on serostatus, despite distinct disease differences between seronegative and seropositive patients. These groups vary in cellular abnormalities, immunologic and genetic profiles, and therapeutic responses. The present study aims to target differences in RA severity, suggesting a need for personalized treatment approaches. A retrospective cohort study of 117 RA patients (seronegative n=55, seropositive n=62) was conducted over four years, during which all patients were treated with combinations of DMARDs. Seronegativity was defined by the absence of rheumatoid factor (RF) and anti-citrullinated protein antibodies (ACPA), while seropositivity was defined by the presence of at least one antibody. Disease severity parameters, including morning stiffness, Health Assessment Questionnaire (HAQ), Disease Activity Score in 28 joints (DAS28), Simplified Disease Activity Index (SDAI), and Visual Analogue Scale (VAS), were assessed annually. Seronegative patients were older, had a higher body mass index, and experienced later disease onset. At baseline, disease severity indicators, including morning stiffness, HAQ, DAS28, SDAI, and VAS, were significantly lower in seronegative patients (p <0.05). Disease severity improved over the years in both groups, with significant changes only in the first year. Autoantibodies like RF and ACPA correlated with more severe disease and a higher risk of unfavorable progression. These findings support personalized therapeutic strategies. Further research should explore whether seronegative RA patients require alternative treatment and rehabilitation due to their milder disease course.